A common molecular mechanism underlies the role of Mps1 in chromosome biorientation and the spindle assembly checkpoint. (19th April 2020) - Benzi, Giorgia; Camasses, Alain; Atsunori, Yoshimura; Katou, Yuki; Shirahige, Katsuhiko; Piatti, Simonetta
Abstract: The Mps1 kinase corrects improper kinetochore–microtubule attachments, thereby ensuring chromosome biorientation. Yet, its critical phosphorylation targets in this process remain largely elusive. Mps1 also controls the spindle assembly checkpoint (SAC), which halts chromosome segregation until biorientation is attained. Its role in SAC activation is antagonised by the PP1 phosphatase and involves phosphorylation of the kinetochore scaffold Knl1/Spc105, which in turn recruits the Bub1 kinase to promote assembly of SAC effector complexes. A crucial question is whether error correction and SAC activation are part of a single or separable pathways. Here, we isolate and characterise a new yeast mutant, mps1‐3, that is severely defective in chromosome biorientation and SAC signalling. Through an unbiased screen for extragenic suppressors, we found that mutations lowering PP1 levels at Spc105 or forced association of Bub1 with Spc105 reinstate both chromosome biorientation and SAC signalling in mps1‐3 cells. Our data argue that a common mechanism based on Knl1/Spc105 phosphorylation is critical for Mps1 function in error correction and SAC signalling, thus supporting the idea that a single sensory apparatus simultaneously elicits both pathways. Synopsis: Through isolation and characterization of the new mps1‐3 mutant, this study proposes that Mps1‐dependent phosphorylation of Spc105 contributes to both proper chromosome segregation and the spindle assembly checkpoint in budding yeast. mps1‐3 temperature‐sensitive mutant fails to correct faulty kinetochore‐microtubule attachments and activate the spindle assembly checkpoint. Mps1‐3 is hyperactive and does not localize at kinetochores. Suppressing mutations reducing PP1 activity at kinetochores restore proper chromosome segregation and checkpoint signalling in mps1‐3 mutant cells. The mps1‐3 mutant is defective in Spc105 phosphorylation and Bub1 kinetochore recruitment. Artificial recruitment of Bub1 to Spc105 rescues the chromosome segregation and checkpoint defects of mps1‐3 cells. Abstract : Through isolation and characterization of the new mps1‐3 mutant, this study proposes that Mps1‐dependent phosphorylation of Spc105 contributes to both proper chromosome segregation and the spindle assembly checkpoint in budding yeast.